Optimization of Endoglucanase Synthesis by Trichoderma harzianum via Taguchi Approach: Taguchi-optimized endoglucanase production by T. harzianum - Hwee Li Teo; Roswanira Abdul Wahab (Journal of Tropical Life Science, 2023)
The oil palm biomass produced by plantations and mills in Malaysia is the largest contributor to the nation’s agro-waste, with the oil palm leaves (OPL) topping the list. Nevertheless, the surplus of OPL might have applicability as the substrate for cultivating lignocellulolytic bio-degraders. Ipso facto, this study employed raw OPL as the carbon source for cultivating Trichoderma harzianum under solid-state fermentation (SSF). Optimization of the SSF process using the Taguchi orthogonal design to produce endoglucanase (CMCase) successfully established the optimal fermentation conditions as the following: 7.00 × 108 spore/g inoculum size, 50% moisture content, pH 12 Mandel’s medium, with 3-day incubation at 40°C. The crude enzyme cocktail exhibited the corresponding maximum activity of 417.49 U/g CMCase. The enzymatic activities were significantly affected by factors, moisture content, inoculum size, and initial pH (p-value < 0.05). In short, the high extracellular CMCase activity of the T. harzianum crude enzyme cocktail may prove valuable in accelerating the saccharification of cellulose for biofuel-and nanocellulose production.